Therapeutic Potential of Semi-Mature Dendritic Cells for Tolerance Induction - Lutz, Manfred B. (Frontiers in Immunology, 2012)
Dendritic cells (DCs) are major players in the control of adaptive tolerance and immunity. Therefore, their specific generation and adoptive transfer into patients or their in vivo targeting is attractive for clinical applications. While injections of mature immunogenic DCs are tested in clinical trials, tolerogenic DCs still are awaiting this step. Besides the tolerogenic potential of immature DCs, also semi-mature DCs can show tolerogenic activity but both types also bear unfavorable features. Optimal tolerogenic DCs, their molecular tool bar and their use for specific diseases still have to be defined. Here, the usefulness of in vitro generated and adoptively transferred semi-mature DCs for tolerance induction is outlined. The in vivo targeting of semi-mature DCs as represented by steady state migratory DCs (ssmDCs) are discussed for treatment of autoimmune diseases and allergies. First clinical trials with transcutaneous allergen application may point to their therapeutic use in the future.